Three new species of ptyctimous mites (Acari: Oribatida: Phthiracaroidea ) from Spain - Niedbała, Wojciech; Starỳ, Josef (Zootaxa, 2011)
Three new species of the superfamily Phthiracaroidea, Austrophthiracarus parainusitatus sp. nov., Atropacarus (Atropacarus) parainsularis sp. nov. and Atropacarus (Atropacarus) parastriculus sp. nov. are described and figured. All species are from soils of the Provinces Galicia and Cantabria in North and North-West Spain. A comparison with the most related species of the genera Austrophthiracarus and Atropacarus is performed. The faunal composition and distribution of all species of the taxons Austrophthiracarus and Atropacarus (Atropacarus) in the Palaearctic region and in the Iberian Peninsula are discussed.